Ocular trauma treated with pars plana vitrectomy: early outcome report - Mansouri, Mohammad Reza (Int J Ophthalmol, 2016)
AIM: To evaluate demographic variables and visual outcomes, among patients with ocular injuries involving the posterior segment, managed with pars plana vitrectomy. METHODS: The records of patients were studied retrospectively from March to September 2010, to determine the age, gender, place of occurrence of trauma, visual acuity, anatomical site, nature of injury, wound length, the presence of an afferent pupillary defect, and the timing of vitrectomy. The Ocular Trauma Score was measured. The minimum follow-up from presentation was 6mo. RESULTS: Ninety patients (77 males, 13 females), with a mean age of 32.7±15.8y were included over the 6-month period. The majority of cases occurred in the workplace (47 patients), followed by home (14 patients). The mean visual acuity (logMAR) of patients significantly improved from 2.36±0.72 preoperatively to 1.50±1.14 postoperatively. Twenty-three patients had preoperative vision better than 2.0 logMAR, the postoperative visual acuity was significantly better among these patients than patients with worse than 2.0 logMAR (P<0.001). Visual improvement between groups with early vitrectomy (<7d) and delayed vitrectomy (>7d) was not significantly different (P=0.66). Postoperative visual acuity was not significantly different between patients with injury in Zone I and II (P=0.64), but patients with injury in Zone III had significantly poorer visual acuity (P=0.02). Patients with relative afferent pupillary defect had significantly poorer postoperative visual acuity (P=0.02). Preoperative visual acuity, the difference of preoperative and postoperative visual acuity, and postoperative visual acuity were significantly different between groups with different ocular trauma scores (P<0.001). CONCLUSION: Trauma is more likely to occur in men under 40y of age and in the workplace. The favorable final visual outcome is associated with the absence of afferent pupillary defect, ocular trauma score and presenting visual acuity as well as the zone of injury, and not associated with the timing of vitrectomy.